Synthetic approaches to the 2010–2014 new agrochemicals. Issue 3 (1st February 2016) - Jeanmart, Stephane; Edmunds, Andrew J.F.; Lamberth, Clemens; Pouliot, Martin
Graphical abstract: Synthesis of benzovindiflupyr (II ) and 29 other agrochemicals reaching the crop protection market. Abstract: In this review, the synthesis of 30 agrochemicals that received an international standardization organization (ISO) name during the last five years (January 2010 to December 2014) is described. The aim is to showcase the range and scope of chemistries used to discover or produce the latest active ingredients addressing the crop protection industry's needs.